DIMENSI TASAWUF PENDIDIKAN ISLAM DAN PENCEGAHAN KEKERASAN TERHADAP ANAK DALAM KELUARGA - Idrus al-Kaf (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2018)
Family is the first and foremost educational institution in human life. Both parents acted as teachers and children as students. In this case, parents, besides being obliged to raise their children physically, are also obliged to mature them psychologically and spiritually. But in reality, the existence of children is often overlooked, even worse, children are often become victims of adult violence and abuse.In fact, violence against children does not only have a negative impact on child development, but also a violation of human rights against children, which includes the right to live, the rights to protection, and the right to education. These rights are those which are the basic rights possessed by every human being as a gift from God which has been carried from the early life.For this reason, efforts to prevent violence against children in the family is necessary, one of which, is to instill mystical values to children as early as possible. Efforts to improve the noble character for children can be adopted from the Quranic teachings and some mystical attitudes and behaviors that aim to instill spiritual values. Every child's mistakes are always controlled by actions and punishments that can remind him of God. Mystical character education is a mystical solution that will play a major role in realizing a moral revolution and spiritual character in society.